2015
DOI: 10.1016/j.solener.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

PV power forecast using a nonparametric PV model

Abstract: Forecasting the AC power output of a PV plant accurately is important both for plant owners and electric system operators. Two main categories of PV modeling are available: the parametric and the nonparametric. In this paper, a methodology using a nonparametric PV model is proposed, using as inputs several forecasts of meteorological variables from a Numerical Weather Forecast model, and actual AC power measurements of PV plants. The methodology was built upon the R environment and uses Quantile Regression For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(72 citation statements)
references
References 18 publications
0
71
0
1
Order By: Relevance
“…Angle of 15°, which was adopted for public building allows for the relative annual energy yield of approximately 818 kWh/kWp. For comparison, the annual energy yield of installed PV system for southern Poland is not less than 942 kWh/kWp [18][19][20].…”
Section: Analysis Of Electricity Production From Photovoltaic Panelsmentioning
confidence: 99%
“…Angle of 15°, which was adopted for public building allows for the relative annual energy yield of approximately 818 kWh/kWp. For comparison, the annual energy yield of installed PV system for southern Poland is not less than 942 kWh/kWp [18][19][20].…”
Section: Analysis Of Electricity Production From Photovoltaic Panelsmentioning
confidence: 99%
“…Unfortunately, their discussion of probability forecasting results does not use any standard metrics and is therefore not directly comparable to our results. In [12], the proposed methodology had a skill score between 33% and 36% depending on the plant examined, for five plants located in northern Spain. The hourly forecast for a 662 kW plant in Northern Italy was evaluated at [15] using several forecasting techniques and an ensemble of the forecasts obtained from these models.…”
Section: Discussionmentioning
confidence: 99%
“…Bracale et al in [11] obtained a probability distribution for predicting the power generated from a Bayesian autoregressive model that takes into account the dependence on solar radiation and some weather variables, such as cloud cover and humidity. Most recently, Almeida et al [12] studied the accuracy of the non-parametric probability forecasts using the quantile regression forest methodology for five PV plants in northern Spain. The authors used different variables of the meteorological model and showed the importance of the radiation data and the scarce utility of the increase in the number of variables used in the modeling.…”
Section: Introductionmentioning
confidence: 99%
“…One way to solve or to reduce this problem is to 41 forecast this PV output power [9]. A good forecast helps the grid manager to plan the other energy 42 capabilities to compensate for the PV plants power variations [10]. The forecasting quality of the 43 ouput PV plant is strongly linked to the global horizontal irradiation (GHI) forecasting accuracy [11].…”
Section: Interest Of Solar Irradiation Forecasting 27 28mentioning
confidence: 99%